Allopatric speciation is more prevalent than parapatric ecological divergence in a recent high-Andean diversification (Linochilus: Asteraceae) - Vargas,Oscar M.; Madriñán,Santiago; Simpson,Beryl (PeerJ, 2023)
Elucidating how species accumulate in diversity hotspots is an ongoing debate in evolutionary biology. The páramo, in the Northern Andes, has remarkably high indices of plant diversity, endemicity, and diversification rates. A hypothesis for explaining such indices is that allopatric speciation is high in the páramo given its island-like distribution. An alternative hypothesis is that the altitudinal gradient of the Andean topography provides a variety of niches that drive vertical parapatric ecological speciation. A formal test for evaluating the relative roles of allopatric and parapatric ecological speciation is lacking. The main aim of our study is to test which kind of speciation is more common in an endemic páramo genus. We developed a framework incorporating phylogenetics, species’ distributions, and a morpho-ecological trait (leaf area) to compare sister species and infer whether allopatric or parapatric ecological divergence caused their speciation. We applied our framework to the species-rich genus Linochilus (63 spp.) and found that the majority of recent speciation events in it (12 events, 80%) have been driven by allopatric speciation, while a smaller fraction (one event, 6.7%) is attributed to parapatric ecological speciation; two pairs of sister species produced inconclusive results (13.3%). We conclude that páramo autochthonous (in-situ) diversification has been primarily driven by allopatric speciation.
Keywords: Allopatric speciation; Parapatric ecological divergence; Andean páramo; Diversification; Linochilus